N Addition Overwhelmed the Effects of P Addition on the Soil C, N, and P Cycling Genes in Alpine Meadow of the Qinghai-Tibetan Plateau - Xiao, Jiannan; Dong, Shikui; Shen, Hao; Li, Shuai; Wessell, Kelly; Liu, Shiliang; Li, Wei; Zhi, Yangliu; Mu, Zhiyuan; Li, Hongbo (Frontiers in Plant Science, 2022)
Although human activities have greatly increased nitrogen (N) and phosphorus (P) inputs to the alpine grassland ecosystems, how soil microbial functional genes involved in nutrient cycling respond to N and P input remains unknown. Based on a fertilization experiment established in an alpine meadow of the Qinghai-Tibetan Plateau, we investigated the response of the abundance of soil carbon (C), N, and P cycling genes to N and P addition and evaluated soil and plant factors related to the observed effects. Our results indicated that the abundance of C, N, and P cycling genes were hardly affected by N addition, while P addition significantly increased most of them, suggesting that the availability of P plays a more important role for soil microorganisms than N in this alpine meadow ecosystem. Meanwhile, when N and P were added together, the abundance of C, N, and P cycling genes did not change significantly, indicating that the promoting effects of P addition on microbial functional genes abundances were overwhelmed by N addition. The Mantel analysis and the variation partitioning analysis revealed the major role of shoot P concentration in regulating the abundance of C, N, and P cycling genes. These results suggest that soil P availability and plant traits are key in governing C, N, and P cycling genes at the functional gene level in the alpine grassland ecosystem.